2014
DOI: 10.1088/0953-4075/47/13/135204
|View full text |Cite
|
Sign up to set email alerts
|

Charge transfer in proton–helium collisions from low to high energy

Abstract: The cross section for charge transfer in proton-helium collisions has been computed in the energy range from 10 eV/u up to 10 MeV/u. Four different methods (full quantal time-independent and time-dependent methods, molecular and atomic basis set semi-classical approaches) valid in different energy regimes have been used to calculate the partial and total cross section for single-electron capture. The results are compared with previous theoretical calculations and experimental measurements and the different the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 77 publications
1
15
0
Order By: Relevance
“…For more recent, but somewhat more specialized accounts we refer the reader to [149,150] These defects can be remedied by including electron translation factors (ETFs) or by using reaction coordinate techniques [151,152]. An alternative method is the hyperspherical close coupling (HSCC) approach, in which a rescaled Schrödinger equation written in terms of hyperspherical coordinates is solved (see ref.…”
Section: Uncertainty Assessment For Charge Transfer Collisionsmentioning
confidence: 99%
“…For more recent, but somewhat more specialized accounts we refer the reader to [149,150] These defects can be remedied by including electron translation factors (ETFs) or by using reaction coordinate techniques [151,152]. An alternative method is the hyperspherical close coupling (HSCC) approach, in which a rescaled Schrödinger equation written in terms of hyperspherical coordinates is solved (see ref.…”
Section: Uncertainty Assessment For Charge Transfer Collisionsmentioning
confidence: 99%
“…(7), (48) REFERENCES.-(1) Burgess & Seaton (1960); (2) Schulz & Asundi (1967); (3) Dunn (1968); (4) Bates & Öpik (1968); (5) Aldrovandi & Péquignot (1973); (6) Osterbrock (1974); (7) Walkauskas & Kaufman (1975); (8) Ramaker & Peek (1976); (9) Samson & Haddad (1994); (29) Peart & Hayton (1994); (30) Stancil (1994); (31) Draine & Bertoldi (1996); (32) Olamba et al (1996); (33) (2010); (50) Loreau et al (2014). † For convenience, the reaction number for photoionization or photodissociation process is shown in boldface.…”
Section: A12 Photoionizationmentioning
confidence: 99%
“…7,8 In that model, additional atomic processes present in the edge and SOL regions plasma conditions such as proton ionization and proton-helium chargeexchange have been included. 9 The forward 1-D kinetic model revealed that electronimpact excitation and ionization are the dominating collisional mechanisms during the emission and depletion of the helium neutral gas as injected for diagnostic purposes. It also showed that interactions between the neutral helium in the gas-puff and protons were several orders of magnitude lower with respect to interactions with electrons, therefore validating the reliability of this powerful diagnostic tool.…”
Section: Introductionmentioning
confidence: 99%
“…Generalized charge-exchange rate-coefficients for the two spin systems of helium [D(nl)+He + → D + +He( 1 S, 3 S)] calculated using equation(9), and T He + = 300K 10. …”
mentioning
confidence: 99%